Less Lumens‐Less Risk: A Pilot Intervention to Increase the Use of Single‐Lumen Peripherally Inserted Central Catheters. Issue 1 (31st October 2018) - Bozaan, David; Skicki, Deanna; Brancaccio, Adamo; Snyder, Ashley; Friebe, Sue; Tupps, Matthew; Paje, David; Chopra, Vineet
Abstract : To reduce risk of complications, existing guidelines recommend use of peripherally inserted central catheters (PICCs) with the minimal number of lumens. This recommendation, however, is difficult to implement in practice. We conducted a pilot study to increase the use of single‐lumen PICCs in hospitalized patients. The intervention included (1) education for physicians, pharmacists, and nurses; (2) changes to the electronic PICC order‐set that set single lumen PICCs as default; and (3) criteria defining when use of multilumen PICCs is appropriate. The intervention was supported by realtime monitoring and feedback. Among 226 consecutive PICCs, 64.7% of preintervention devices were single lumen versus 93.6% postintervention ( P < .001). The proportion of PICCs with an inappropriate number of lumens decreased from 25.6% preintervention to 2.2% postintervention ( P < .001). No cases suggesting inadequate venous access or orders for the placement of a second PICC were observed. Implementing a single‐lumen PICC default and providing education and indications for multilumen devices improved PICC appropriateness.